Anti-vector immune responses to an MVA vaccine - Muller, Tracey (Division of Virology, 2015)
This study characterised the humoral and cellular immune responses to MVA from a candidate MVA-vectored HIV vaccine in non-human primates, and examined the effect of anti-vector immunity on the response to the HIV immunogens.